Prefabricated CAD/CAM zirconia membrane versus contour augmentation with early implant placement in the anterior maxilla: a randomized controlled clinical trial - Mohammed Mashhout Anas; Amr Mostafa Gabr; Yasser El-Makaky; Mohamed H. Helal (International Journal of Implant Dentistry, 2026)
Abstract Background Horizontal ridge deficiencies in the anterior maxilla frequently compromise ideal implant positioning and esthetic outcomes. This randomized controlled clinical trial evaluated the clinical performance of customized CAD/CAM zirconia membranes compared with conventional collagen membranes for guided bone regeneration (GBR) performed simultaneously with early implant placement. Methods Twenty systemically healthy patients requiring single-tooth replacement in the anterior maxilla underwent early implant placement (4–8 weeks after tooth extraction) combined with simultaneous contour augmentation using a composite graft of autogenous bone and deproteinized bovine bone mineral (1:1). Participants were randomly assigned to receive either a customized CAD/CAM zirconia membrane (test group, n = 10) or a double-layer collagen membrane (control group, n = 10). The primary outcome was horizontal bone gain (HBG) at 6 months, assessed by standardized CBCT superimposition. Secondary outcomes included soft tissue healing evaluated using the Modified Wound Healing Index (MWHI), membrane exposure (wound dehiscence), and patient-reported postoperative pain assessed using a visual analogue scale (VAS). Results All implants survived during the 6-month follow-up period (100% survival rate). Mean HBG was 6.18 ± 0.60 mm in the test group and 5.85 ± 0.37 mm in the control group, with no statistically significant difference between groups ( p = 0.158). Membrane exposure occurred in all patients receiving customized zirconia membranes (10/10, 100%), whereas no membrane exposure was observed in the collagen membrane group (0/10, 0%). Despite the higher exposure rate, graft stability and horizontal bone regeneration were not adversely affected. Soft tissue healing was significantly more favorable in the collagen membrane group. Postoperative pain decreased significantly over time in both groups, with no significant intergroup differences. Conclusions Customized CAD/CAM zirconia membranes achieved horizontal bone augmentation comparable to conventional collagen membranes when used for simultaneous GBR during early implant placement. Although customized zirconia membranes were associated with a substantially higher membrane exposure rate, regenerative outcomes and implant survival remained unaffected, indicating that customized rigid barriers may represent a predictable alternative for horizontal ridge augmentation while offering potential advantages in surgical precision and procedural efficiency. Trial registration : ClinicalTrials.gov NCT06987149.